PERANCANGAN MODEL PENERIMAAN DAN EVALUASI PESANAN PADA INDUSTRI KEMASAN KARTON YANG BERBASISKAN MAKE TO ORDER - Nora Azmi; Irawadi Jamaran; Yandra Arkeman; Djumali Mangunwidjaja (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
Nowadays, carton boxes are very popularly used, mostly in food industries, pharmacy and other consumer products. Most carton box industries work base on customer order (Make-to-order company), because most of carton box order are prepared for particular customer. Carton box are not only used for containing and protecting the product, but also functioned to inform the product to the customers. Make-to-order company has a high level of uncertainty such as the type and design of the product, the step of production, production time, cost, equipments and machine. This could create further problems; the overdue of order and completing process, and the acceptability of the product. This research is intended to design an order processing model for the carton box industry to accelerate order receipt process and evaluate the feasibility of the order. This paper focused on two models, those are the order entry model and order evaluation model. In order entry model, product code is given, and calculation model for needed raw material is made by using mathematical formulation. In order evaluation model, expert system and decision tree are used for analyzing the process capability and selecting machinery as well as designing the steps of production.